Solution of some parabolic inverse problems by homotopy analysis method - Onyejekwe, Ogugua (International Journal of Applied Mathematical Research, 2014)
In this paper, three types of parabolic inverse problems are solved by homotopy analysis method (HAM).  In order to solve these types of problems, an overspecified boundary condition is given.  There are advantages to using HAM, firstly it is independent of small/large physical parameters, there is always a guarantee of convergence; there is flexibility on the choice of base function and initial guess of solution and lastly there is great generality. The numerical results obtained from this method indicate high accuracy and a strong rate of convergence.   Keywords: Control Function, Homotopy Analysis Method, One-Dimensional Heat Equation, Parabolic Inverse Problem.